Impact of Economic Growth on Human Capital, Work Participation, and Emission Reductions: Case Study in Indonesia - Murniati Murniati; Ema Sulisnaningrum; Eddy Priyanto (AIBPM Publisher, 2023)
Investments are influenced by the level of education and work participation in Indonesia; this happens the same with Human Capital. The importance of human capital and investment can have an impact on economic growth and emission reductions. Based on the results of previous studies, the demand for studies on economic growth, human capital, labor participation, and emission reductions is increasing. To determine the causal link between variables, this study used